Composite and electrical / electronic part

A composite material with laminated Ni and Cu layers on a Fe-based alloy substrate addresses manufacturing constraints and interface contamination issues, providing enhanced mechanical properties and conductivity for electronic components.

JP2025018127APending Publication Date: 2025-02-06FURUKAWA ELECTRIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023121578
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Existing clad materials with copper and stainless steel layers face manufacturing constraints due to high temperature and pressure requirements, and have a high likelihood of foreign matter contamination at the interface, making them unsuitable for small parts applications.

Method used

A composite material is created by laminating Ni-containing and Cu-containing layers on a Fe-based alloy substrate, with specific thickness ratios and grain sizes, allowing for high adhesion and formation without high-pressure or high-temperature processing.

Benefits of technology

The composite material achieves a balance of high mechanical properties and conductivity with improved adhesion to the substrate, suitable for use in electrical and electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018127000001_ABST
    Figure 2025018127000001_ABST
Patent Text Reader

Abstract

To provide a composite with a Cu-containing layer having an excellent balance in terms of both high mechanical properties and high electrical conductivity, as well as high adhesion to a substrate, and an electrical / electronic part using this composite.SOLUTION: The present invention provides a composite that comprises Ni-containing layers and Cu-containing layers stacked in this order on one or both sides of a conductive substrate made of Fe-based alloy, and the total thickness of the Cu-containing layers is 10 μm or more in view from the cross section including the thickness direction of the composite, and the ratio of the cross-sectional area of the Cu-containing layer to the total cross-sectional area of the composite is between 0.20 and 0.60 inclusive. The present invention also provides an electrical / electronic part that comprises the inventive composite.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite material and an electric / electronic component. [Background technology]

[0002] A clad material in which a stainless steel layer and a copper layer are bonded together is known as a material that has both high mechanical properties and electrical conductivity, and thus has an excellent balance between high mechanical properties and high thermal conductivity.

[0003] For example, Patent Document 1 describes a composite metal plate for heat diffusion having an overall thickness of 500 μm or less, in which a first copper layer, a stainless steel layer, and a second copper layer are bonded in that order, in which, when the thickness of the first copper layer is Tc1, the thickness of the stainless steel layer is Ts, and the thickness of the second copper layer is Tc2, the thickness ratio calculated by Ts / (Tc1+Tc2) is 0.2 or more and 5 or less, and when the thermal conductivity of the composite metal plate in the planar direction is Kx and the thermal conductivity of the composite metal plate in the thickness direction is Kz, the thermal conductivity ratio calculated by Kx / Kz is 4.4 or more and 6.8 or less.

[0004] Patent Document 2 also describes a clad material made of stainless steel as a base material, with Ni or a Ni alloy pressure-welded to one main surface of the base material and Cu pressure-welded to the other main surface, in which the thickness of the stainless steel is more than 92% and not more than 99% of the overall thickness of the clad material, and the tensile strength is 70 kgf / mm 2 The above high strength clad materials have been described, and a method for producing clad materials having excellent tensile strength by cold welding alone is known. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2020-025097 A [Patent Document 2] Japanese Patent Application Publication No. 11-104856 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the clad material in which a copper layer and a stainless steel layer are bonded together as described in Patent Document 1, there are problems in that when bonding the copper layer and the stainless steel layer, thermal diffusion at high temperatures is required and processing is required under high pressure, resulting in many manufacturing constraints.In addition, in the clad material in which a copper layer and a stainless steel layer are bonded together as described in Patent Document 2, there is a high possibility that foreign matter will be contained at the interface between the copper layer and the stainless steel layer, which will reduce the adhesion between the copper layer and the stainless steel layer, making it unsuitable for use in applications, particularly for micro-components.

[0007] The present invention aims to provide a composite material having a Cu-containing layer that has an excellent balance of high mechanical properties and high electrical conductivity and also has high adhesion to a substrate, and an electric / electronic component using the same. [Means for solving the problem]

[0008] The present inventors have found that by laminating a Ni-containing layer and a Cu-containing layer in this order on one or both sides of a conductive substrate made of an Fe-based alloy, the adhesion between the Fe-based alloy and the Cu-containing layer can be improved even when the layers are formed only by a cold process. In addition, by making the thickness of the Cu-containing layer of this composite material 10 μm or more on one or both sides in total, and by making the ratio of the cross-sectional area of ​​the Cu-containing layer to the total cross-sectional area of ​​the composite material within the range of 0.20 to 0.60, the tensile strength and electrical conductivity of the composite material can be increased, thereby improving both the mechanical properties and electrical conductivity of the composite material, and have completed the present invention.

[0009] (1) A composite material comprising a conductive substrate made of an Fe-based alloy, on one or both sides of which a Ni-containing layer and a Cu-containing layer are laminated in this order, the Cu-containing layers having a total thickness of 10 μm or more when viewed in a cross section including the thickness direction of the composite material, and the ratio of the cross-sectional area of ​​the Cu-containing layers to the total cross-sectional area of ​​the composite material is 0.20 or more and 0.60 or less.

[0010] (2) The composite material according to (1) above, wherein the Fe-based alloy is an Fe-Ni-Cr-based or Fe-Ni-based alloy.

[0011] (3) The composite material according to (1) or (2) above, wherein the Ni-containing layer has crystal grains with an average crystal grain size of 1.00 μm or less.

[0012] (4) The composite material according to any one of (1) to (3) above, wherein, when the lamination interface between the Ni-containing layer and the Cu-containing layer is viewed in the cross section, a ratio of a total length of a portion of the lamination interface, in which Ni crystal grains constituting the Ni-containing layer and Cu crystal grains constituting the Cu-containing layer facing the Ni crystal grains across the lamination interface have the same crystal orientation, to a total length of the lamination interface in a measurement region is 0.2 or more.

[0013] (5) The composite material according to any one of (1) to (4) above, wherein the conductive substrate has a Vickers hardness (HV) of 300 or more.

[0014] (6) An electric / electronic component comprising the composite material according to any one of (1) to (5) above. Effect of the Invention

[0015] According to the present invention, it is possible to provide a composite material having an excellent balance of high mechanical properties and high electrical conductivity, and including a Cu-containing layer having high adhesion to a substrate, and an electric / electronic component using the same. [Brief description of the drawings]

[0016] [Figure 1] 1 is a schematic diagram showing a main part of a cross section of a composite material according to one embodiment of the present invention when cut along a plane including a thickness direction. [Diagram 2] 1 is a scanning ion microscope (SIM) image of a cross section including the thickness direction of a composite material of Example 9 of the present invention observed with a SIM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, preferred embodiments of the composite material and the electric / electronic component of the present invention will be described in detail.

[0018] <About composite materials> Fig. 1 is a schematic diagram showing a main part of a cross section of a composite material according to an embodiment of the present invention when the composite material is cut in a plane including the thickness direction. As shown in Fig. 1, the composite material 1 of the present invention is a composite material in which Ni-containing layers 31, 32 and Cu-containing layers 41, 42 are laminated in this order on one or both sides of a conductive substrate 2 made of an Fe-based alloy, and the thicknesses t1, t2 of the Cu-containing layers 4 are 10 μm or more in total (t1+t2) when viewed in a cross section including the thickness direction of the composite material 1, and the ratio of the cross-sectional area of ​​the Cu-containing layers 4 to the total cross-sectional area of ​​the composite material 1 is 0.20 or more and 0.60 or less.

[0019] In this way, by laminating the Ni-containing layers 31, 32 and the Cu-containing layers 41, 42 in this order on one or both sides of the conductive substrate 2 made of an Fe-based alloy, the adhesiveness between the conductive substrate 2 and the Cu-containing layers 41, 42 can be improved. In addition, by setting the thicknesses t1, t2 of the Cu-containing layers 41, 42 of the composite material 1 to 10 μm or more in total (t1+t2) on one or both sides, and setting the ratio of the cross-sectional area of ​​the Cu-containing layers to the total cross-sectional area of ​​the composite material 1 to a range of 0.20 to 0.60, the tensile strength and electrical conductivity of the composite material 1 can be increased, thereby improving both the mechanical properties and electrical conductivity of the composite material 1. Therefore, it is possible to provide a composite material 1 having Cu-containing layers 41, 42 that have an excellent balance in terms of both high mechanical properties and electrical conductivity and have high adhesiveness to the conductive substrate 2, and an electric / electronic component using the composite material.

[0020] Here, when the front surface 41a and the back surface 41b of the Cu-containing layer 41 are both flat, the front surface 42a and the back surface 42b of the Cu-containing layer 42 are both flat, and the front surface 1a and the back surface 1b of the composite material 1 are both flat, the ratio of the cross-sectional area of ​​the Cu-containing layer to the total cross-sectional area of ​​the composite material 1 may be approximated by the ratio of the sum (t1+t2) of the thicknesses of the Cu-containing layers 41 and 42 to the thickness t0 of the composite material 1. On the other hand, at least any one of the front surfaces 41a and 42a of the Cu-containing layers 41 and 42, the back surfaces 41b and 42b of the Cu-containing layers 41 and 42, and the front surface 1a and the back surface 1b of the composite material 1 may be configured by a curved surface.

[0021] The composite material 1 of the present invention is formed by laminating Ni-containing layers 31, 32 and Cu-containing layers 41, 42 in this order on one or both sides of a conductive substrate 2 made of an Fe-based alloy.

[0022] (Conductive substrate)

[0023] The conductive base 2 has a plate shape, and has two surfaces, a front surface 2a and a back surface 2b, as well as an end surface 2c and a side surface (not shown) connecting the two surfaces together.

[0024] The conductive substrate 2 is made of an Fe-based alloy. Here, the Fe-based alloy is preferably an alloy containing one or both of nickel (Ni) and chromium (Cr), and from the viewpoint of increasing the mechanical strength, it is preferable to use an Fe-Ni-Cr-based or Fe-Ni-based alloy. Among these, an example of the Fe-Ni-based alloy is 42 alloy (Fe-42 mass% Ni). Also, an example of the Fe-Ni-Cr-based alloy is stainless steel such as SUS301, SUS304, and SUS630. As these Fe-Ni-Cr-based and Fe-Ni-based alloys, those produced by melting and casting may be used. Also, as the Fe-Ni-based alloy, those produced by electroplating may be used.

[0025] The thickness t5 of the conductive base 2 is not particularly limited, but can be, for example, in the range of 10 μm or more and 100 μm or less, from the viewpoint of providing sufficient mechanical strength to the composite material 1 and from the viewpoint of achieving a low profile and small size of an electrical / electronic component including the composite material.

[0026] Moreover, the conductive base 2 preferably has a Vickers hardness (HV) of 300 or more, more preferably 330 or more, and even more preferably 350 or more. Such a conductive base 2 has a high tensile strength in proportion to its hardness, and therefore the tensile strength of the composite material 1 in which Ni-containing layers 31, 32 and Cu-containing layers 41, 42 described below are laminated on the conductive base 2 can be further increased.

[0027] Here, the Vickers hardness (HV) can be measured in the cross section including the thickness direction of the conductive substrate, for example, according to the Vickers hardness test method described in JIS Z2244 (2009). More specifically, the Vickers hardness (HV) can be measured when the load (test force) when the diamond indenter is pressed into the cross section including the thickness direction of the conductive substrate 2, which is the test piece, is 0.049N, and the pressing time of the indenter is 15 seconds.

[0028] (Regarding Ni-containing layer) The Ni-containing layers 31 and 32 are layers formed on one or both sides of the conductive substrate 2 (both the front surface 2a and the back surface 2b in FIG. 1).

[0029] In the composite material 1 of the present invention, the Ni-containing layers 31 and 32 are formed between the conductive substrate 2 made of an Fe-based alloy and the Cu-containing layers 41 and 42 described below, respectively, thereby improving the adhesion between the conductive substrate 2 and the Cu-containing layers 41 and 42. In this regard, if the Cu-containing layers 41 and 42 are formed directly on the surface of the conductive substrate 2, the Cu-containing layers 41 and 42 are likely to peel off when processed later. Therefore, in the composite material 1 of the present invention, it is necessary to form the Ni-containing layers 31 and 32 between the conductive substrate 2 and the Cu-containing layers 41 and 42.

[0030] The material of the Ni-containing layers 31 and 32 is preferably nickel (Ni) or a Ni-based alloy. More preferably, from the viewpoint of further improving the adhesive strength between the conductive base 2 and the Cu-containing layers 41 and 42, the Ni-containing layers 31 and 32 are preferably made of Ni or a Ni-based alloy containing 99.8 mass % or more of Ni with the remainder being unavoidable impurities.

[0031] The Ni-containing layers 31 and 32 preferably have crystal grains with an average crystal grain size of 1.00 μm or less. By reducing the average crystal grain size of the crystal grains contained in the Ni-containing layers 31 and 32, the adhesion of the Cu-containing layers 41 and 42 formed on the Ni-containing layers 31 and 32 can be further improved. In particular, since the Cu-containing layers 41 and 42 formed on the Ni-containing layers 31 and 32 are the softest of the substances constituting the composite material 1, by reducing the average crystal grain size of the crystal grains contained in the Ni-containing layers 31 and 32, peeling or cracking of the Cu-containing layers 41 and 42 due to processing when forming the composite material 1 can be made less likely to occur. In addition, by reducing the average crystal grain size of the crystal grains contained in the Ni-containing layers 31 and 32, the average crystal grain size of the crystal grains contained in the Cu-containing layers 41 and 42 can also be reduced.

[0032] The average crystal grain size in the Ni-containing layers 31, 32 can be measured by forming a cross section including the thickness direction of the composite material 1 using a focused ion beam (FIB) device (e.g., FB2000A manufactured by Hitachi, Ltd.), observing the cross section using a scanning ion microscope (Scanning Ion Microscope, manufactured by Seiko Instruments Inc., model number: SMI3050TB), and counting the number of points where lines parallel to the substrate surface intersect with the boundaries of crystal grains from the channeling contrast (crystal orientation information) that appears in the resulting scanning ion microscope (SIM) image. The average grain size can then be determined by a cutting method in which the average length of each section of the lines defined by the boundaries of the crystal grains is determined.

[0033] The thickness of the Ni-containing layers 31, 32 is not particularly limited, but is preferably 0.05 μm or more in total when laminated on one or both sides of the conductive base 2. Among them, from the viewpoint of suppressing an increase in the material cost of the composite material 1, the total thickness of the Ni-containing layers 31, 32 may be 2.00 μm or less.

[0034] 1, when Ni-containing layers 31 and 32 are formed on both sides of conductive substrate 2, the total thickness of the Ni-containing layers formed on one or both sides of the conductive substrate can be the total of thickness t3 of Ni-containing layer 31 and thickness t4 of Ni-containing layer 32. On the other hand, when a Ni-containing layer is formed on only one side of conductive substrate 2, the total thickness of the Ni-containing layers formed on one or both sides of the conductive substrate can be the thickness of that Ni-containing layer (not shown).

[0035] (About Cu-containing layer) The Cu-containing layers 41 and 42 are layers formed on one or both sides (both the front surface 2a and the back surface 2b in FIG. 1) of the conductive base 2 after the Ni-containing layers 31 and 32. That is, the Cu-containing layers 41 and 42 are layers formed on a part or the whole of the surfaces of the Ni-containing layers 31 and 32 that are not in contact with the conductive base 2.

[0036] In the composite material 1 of the present invention, the Cu-containing layers 41, 42 are respectively formed on the conductive substrate 2 made of an Fe-based alloy with the Ni-containing layers 31, 32 interposed therebetween, thereby making it possible to enhance the adhesion of the Cu-containing layers 41, 42 to the conductive substrate 2.

[0037] The material of the Cu-containing layers 41 and 42 is preferably copper (Cu) or a Cu-based alloy. More preferably, from the viewpoint of further improving the tensile strength and electrical conductivity of the composite material 1, the Cu-containing layers 41 and 42 are preferably made of Cu or a Cu-based alloy containing 99.8 mass % or more of Cu with the remainder being unavoidable impurities.

[0038] When viewed in a cross section including the thickness direction of the composite material 1, the Cu-containing layers 41, 42 have a total thickness of 10 μm or more. If the Cu-containing layers 41, 42 have a thickness less than 10 μm, the springback increases during fine bending, making it difficult to use the layers in electric and electronic components. On the other hand, the upper limit of the thickness of the Cu-containing layers 41, 42 is not particularly limited, but may be 100 μm or less in total from the viewpoint of more efficiently producing the composite material 1.

[0039] 1, when Cu-containing layers 41, 42 are formed on both sides of conductive substrate 2, the total thickness of the Cu-containing layers formed on one or both sides of the conductive substrate can be the total of thickness t1 of Cu-containing layer 41 and thickness t2 of Cu-containing layer 42. On the other hand, when a Cu-containing layer is formed on only one side of conductive substrate 2, the total thickness of the Cu-containing layers formed on one or both sides of the conductive substrate can be the thickness of that Cu-containing layer (not shown).

[0040] In the composite material 1 of the present invention, the ratio of the cross-sectional area of ​​the Cu-containing layers 41, 42 to the total cross-sectional area of ​​the composite material 1 is in the range of 0.20 to 0.60 when viewed in a cross section including the thickness direction Y. This makes it possible to increase the tensile strength and electrical conductivity of the composite material, thereby increasing both the mechanical properties and electrical conductivity of the composite material 1. Here, if the ratio of the cross-sectional area of ​​the Cu-containing layers 41, 42 to the total cross-sectional area of ​​the composite material 1 is less than 0.2, the electrical conductivity of the composite material 1 is insufficient. On the other hand, if the ratio of the cross-sectional area of ​​the Cu-containing layers 41, 42 to the total cross-sectional area of ​​the composite material 1 exceeds 0.6, the mechanical strength of the composite material 1 is insufficient.

[0041] Furthermore, from the viewpoint of further enhancing the peeling resistance of the composite material 1, it is preferable that the crystal orientations of the Ni-containing layers 31, 32 and the Cu-containing layers 41, 42 adjacent to each other through the lamination interfaces 51, 52 are highly identical. More specifically, when the lamination interfaces 51, 52 of the Ni-containing layers 31, 32 and the Cu-containing layers 41, 42 are viewed in a cross section including the thickness direction Y as shown in Fig. 1, the composite material 1 has a portion L1-L2 of the lamination interfaces in which the Ni crystal grains 33, 34 constituting the Ni-containing layers 31, 32 and the Cu crystal grains 43, 44 constituting the Cu-containing layers 41, 42 facing the Ni crystal grains 33, 34 across the lamination interfaces 51, 52 have the same crystal orientation relative to the entire length (2 x L0) of the lamination interfaces 51, 52 in the measurement region 10. 10 The total length when the lengths of the 10 ) is preferably 0.2 or more. This makes the deformation behavior of the Ni-containing layers 31, 32 and the Cu-containing layers 41, 42 similar to each other, so that peeling of the Cu-containing layers 41, 42 from the Ni-containing layers 31, 32 can be suppressed.

[0042] The difference or similarity of the crystal orientations of the Ni crystal grains 33, 34 and the Cu crystal grains 43, 44 located on either side of the lamination interfaces 51, 52 was confirmed by forming a cross section including the thickness direction of the composite material 1 using a focused ion beam (FIB) device (e.g., FB2000A manufactured by Hitachi, Ltd.), observing the cross section using a scanning ion microscope (Scanning Ion Microscope, manufactured by Seiko Instruments Inc., model number: SMI3050TB), and using the channeling contrast (crystal orientation information) that appears in the obtained scanning ion microscope (SIM) image. Here, when the Ni crystal grains 33, 34 having a dark color in the Ni-containing layers 31, 32 and the Cu crystal grains 43, 44 having a dark color in the Cu-containing layers 41, 42 are located on either side of the lamination interfaces 51, 52, the portions of the lamination interfaces 51, 52 where they are located on either side were determined to be portions of the lamination interfaces having the same crystal orientation. Similarly, when the Ni crystal grains 33, 34 of the Ni-containing layers 31, 32, which are light in color, and the Cu crystal grains 43, 44 of the Cu-containing layers 41, 42, which are light in color, are positioned across the lamination interfaces 51, 52, the portions of the lamination interfaces 51, 52 that are positioned across them are also included in the portions of the lamination interfaces having the same crystal orientation. Note that in FIG. 1, the portions L1 to L2 of the lamination interfaces having the same crystal orientation are 10 For ease of explanation, Ni crystal grains 33 and 34 and Cu crystal grains 43 and 44 positioned on either side of the Ni crystal grains 33 and 34 are hatched to distinguish them from other crystal grains.

[0043] (Surface coating layer) The composite material 1 of the present invention may further have at least one surface coating layer (not shown) containing Ni, Sn, Ag, Au, Pd, In or Pt, which is laminated on the Cu-containing layers 41, 42. This allows the characteristics of the front surface 1a or back surface 1b of the composite material 1 to be more suitably adjusted.

[0044] <About the manufacturing method of composite materials> The manufacturing method of the above-mentioned composite material 1 is not particularly limited, but may be a method in which a conductive substrate 2 with a size and thickness adjusted in advance is prepared, electrolytic degreasing and pickling are performed as pretreatment, and then the Ni-containing layers 31, 32 and the Cu-containing layers 41, 42 are formed by electroplating. That is, the manufacturing method of the composite material 1 includes at least a degreasing step, an activation step, a Ni-containing layer forming step, and a Cu-containing layer forming step. As a result, the above-mentioned composite material 1 can also be formed only by a cold process such as electroplating. Note that it is preferable to include a water washing step between any one of the above-mentioned steps and the next step, if necessary.

[0045] (i) Degreasing process The degreasing step and the activation step described below are preferably carried out from the viewpoint of increasing the adhesion between the conductive base 2 and the Ni-containing layers 31 and 32. The degreasing step may include, for example, cathodic electrolytic degreasing. An example of the solution composition and processing conditions used in the cathodic electrolytic degreasing is shown below. [Electrolytic degreasing solution composition and processing conditions] Treatment solution: Sodium orthosilicate 100g / liter Processing temperature: 60℃ Cathode current density: 2.5A / dm 2 Processing time: 10 seconds

[0046] (ii) Activation step An example of the liquid composition and treatment conditions used in the activation step is shown below. [Activation treatment solution composition and treatment conditions] Processing solution: 10% hydrochloric acid Processing temperature: 30℃ Immersion time: 10 seconds

[0047] (iii) Ni-containing layer formation step In the Ni-containing layer forming step, the Ni-containing layers 31, 32 are formed by electroplating on at least one of the two surfaces of the conductive base 2. That is, the Ni-containing layers 31, 32 can be formed by electroplating layers. This allows the Ni-containing layers 31, 32 to be formed by a cold process without requiring processing at high temperature and high pressure.

[0048] In the Ni-containing layer forming step, the crystal grains contained in the Ni-containing layers 31 and 32 can be made fine by strongly stirring the plating solution during electroplating and increasing the current density. An example of the liquid composition and processing conditions used in the Ni-containing layer forming step is shown below.

[0049] [Liquid composition and processing conditions for forming Ni-containing layer] Treatment solution: Nickel chloride 250g / L, Free hydrochloric acid 50g / L Processing temperature: 60℃ Current density: 8A / dm 2 Stirring: Strong Plating thickness: 0.01μm~1.0μm Processing time: Adjust the time for each plating thickness

[0050] (iv)Cu-containing layer formation process In the Cu-containing layer forming step, the Cu-containing layers 41 and 42 are formed by electroplating on the surfaces of the Ni-containing layers 31 and 32. That is, the Cu-containing layers 41 and 42 can also be formed by electroplating layers. Thus, like the Ni-containing layers 31 and 32, the Cu-containing layers 41 and 42 can also be formed by a cold process without requiring processing at high temperature and high pressure.

[0051] In the Cu-containing layer formation process, two-stage electroplating is performed, and by weakening the stirring in the first stage of electroplating and increasing the amount of copper sulfate contained in the treatment solution, it is possible to improve the adhesion to the Ni-containing layers 31, 32 and to improve the identity of the crystal orientation with the Ni crystal grains 33, 34 of the adjacent Ni-containing layers 31, 32 via the lamination interfaces 51, 52. In the Cu-containing layer formation process, an example of the solution composition and processing conditions used in the first and second electroplating steps is shown below.

[0052] [The solution composition and processing conditions for the first electroplating step in the Cu-containing layer formation process] Treatment solution: Copper sulfate 200g / L, Free sulfuric acid 60g / liter, Free hydrochloric acid 50g / L Processing temperature: 30℃ Current density: 1A / dm 2 Stirring: weak Plating thickness: 0.01μm~0.1μm Processing time: Adjust the time for each plating thickness

[0053] [The solution composition and processing conditions for the second electroplating step in the Cu-containing layer formation process] Treatment solution: Copper sulfate 150g / liter, Free sulfuric acid 100g / liter, Free hydrochloric acid 50g / L Processing temperature: 30℃ Current density: 5A / dm 2 Stirring: Strong Plating thickness: up to the specified thickness Processing time: Adjust the time for each plating thickness

[0054] (v) Other processes After the Cu-containing layer forming step, a surface coating layer forming step may be performed in which at least one surface coating layer containing Ni, Sn, Ag, Au, Pd, In or Pt is formed on the surface of the Cu-containing layers 41, .

[0055] After the Cu-containing layer forming step, a cold working step may be performed in which processing such as cold rolling is performed. This makes it possible to obtain a composite material 1 with improved smoothness on the front surface 1a and the back surface 1b. The total working rate in this cold working step is preferably 3% or more and 30% or less.

[0056] Here, the "working rate" is a value obtained by subtracting the cross-sectional area after cold working from the cross-sectional area before working, dividing the result by the cross-sectional area before working, and multiplying the result by 100, and expressed as a percentage, and is expressed by the following formula. [Processing rate] = {([Cross-sectional area before processing] - [Cross-sectional area after processing]) / [Cross-sectional area before processing]} x 100 (%)

[0057] <Applications of composite materials> The composite material 1 of the present invention can be used, for example, in electric and electronic components that include the above-mentioned composite material. Examples of the electric and electronic components include connectors, switches, relays, shielding cases, and flexible flat cables. By using the composite material 1 of the present invention in such electric and electronic components, both the mechanical properties and the conductivity of the electric and electronic components can be improved, making it possible to reduce the size and weight of the electric and electronic components.

[0058] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and includes all aspects encompassed by the concept of the present invention and the scope of the claims, and can be modified in various ways within the scope of the present invention. EXAMPLES

[0059] Next, in order to further clarify the effects of the present invention, examples of the present invention and comparative examples will be described, but the present invention is not limited to these examples of the present invention.

[0060] (Examples 1 to 13 of the present invention, Comparative Examples 1 to 5) A conductive substrate 2 made of the type of metal or alloy shown in Table 1 and having the thickness and Vickers hardness shown in Table 1 was prepared, and pressed to a size of 20 cm length x 6 cm width. Of these, for invention examples 12 and 13 and comparative example 5, 42 alloy (Fe-42 mass% Ni) formed by electroplating under the conditions shown below was used.

[0061] Here, when forming the conductive substrate 2 by electroplating, an aqueous solution containing nickel chloride with a nickel (Ni) metal concentration of 40 g / L, iron (II) sulfate with an iron (Fe) metal concentration of 83 g / L, 30 g / L boric acid, 2 g / L sodium saccharin dihydrate, and 5 g / L malonic acid was prepared as the electroplating solution. Next, a stainless steel plate (SUS304) measuring 20 cm in length and 6 cm in width was placed in the plating electrolytic tank as a cathode electrode, and a pure Ni plate and a pure Fe plate measuring 20 cm in length and 6 cm in width were placed in an anode bag as anode electrodes facing both sides of the plate surface of the cathode electrode. 1 liter of electroplating solution was poured into the tank, and the plating was performed at a temperature of 50° C. with a stirrer rotation speed set to 100 rpm while stirring at 4 A / dm 2 By passing a current at a current density of 1000 .mu.m, an alloy was deposited on the cathode by electroplating to a thickness shown in Table 1. The obtained alloy was then peeled off from the cathode to obtain a conductive base 2 consisting of an electroplated layer.

[0062] These conductive substrates 2 were subjected to cathodic electrolytic degreasing and activation treatment as pretreatment.

[0063] Here, the cathodic electrolytic degreasing is carried out by heating an aqueous solution of sodium orthosilicate with a concentration of 100 g / liter as a degreasing solution in an electrolytic cell, immersing the conductive substrate 2 in the degreasing solution heated to 60° C. and connecting it to the anode of the electrolytic cell, and applying a current of 2.5 A / dm 2 The treatment was carried out by passing a current at a current density of 0.01 to 0.01 for 10 seconds.

[0064] The activation treatment was performed by immersing the conductive substrate 2 after cathodic electrolytic degreasing in 10 mass % hydrochloric acid at 30° C. for 10 seconds.

[0065] Thereafter, for Inventive Examples 1 to 13 and Comparative Examples 2 to 5, Ni-containing layers 31 and 32 were formed on the front surface 2a and rear surface 2b of the conductive substrate 2 by electroplating under the conditions shown below. Among these, for Inventive Examples 3 and 4, the rear surface 2b of the conductive substrate 2 was masked with tape to prevent the Ni-containing layer 32 from being formed on the rear surface 2b of the conductive substrate 2. For Inventive Examples 9 and 10, the rear surface 2b of the conductive substrate 2 was masked with tape to form the Ni-containing layer 31 on the front surface 2a of the conductive substrate 2, and then the masking was removed, and the Ni-containing layers 31 and 32 were further formed on the front surface 2a and rear surface 2b of the conductive substrate 2, thereby forming the Ni-containing layers 31 and 32 having different thicknesses on the front surface 2a side and rear surface 2b side of the conductive substrate 2. On the other hand, for Comparative Example 1, the Ni-containing layers 31 and 32 were not formed on the conductive substrate 2.

[0066] Here, when forming the Ni-containing layers 31 and 32 by electroplating, an aqueous solution containing nickel chloride with a nickel (Ni) metal concentration of 250 g / L and 50 g / L of free hydrochloric acid was prepared as an electroplating solution. Next, a plate-shaped conductive substrate with dimensions of 20 cm length x 6 cm width was placed in a plating electrolytic tank as a cathode electrode, and a plate-shaped pure Ni plate with dimensions of 20 cm length x 6 cm width was placed as an anode electrode facing both plate surfaces of the cathode electrode. 1 L of electroplating solution was poured into the tank, and the plating solution was stirred at a temperature of 60°C with a stirrer rotation speed set to 350 rpm to 550 rpm at 8 A / dm. 2 The Ni-containing layers 31 and 32 having the thicknesses shown in Table 1 were formed by electroplating by passing a current at a current density of 1 A / dm. 2 By passing a current at a current density of 1000 .mu.m, Ni-containing layers 31 and 32 having thicknesses shown in Table 1 were formed by electroplating.

[0067] Next, Cu-containing layers 41 and 42 were formed on the front surface 2a side and the back surface 2b side of the conductive substrate 2 by electroplating under the conditions shown below. Among these, in the present invention examples 3 and 4, the back surface 2b of the conductive substrate 2 was masked with tape to prevent the Cu-containing layer 42 from being formed on the back surface 2b side of the conductive substrate 2. In addition, in the present invention examples 5, 6, 9, and 10 and the comparative examples 2 and 5, the Ni-containing layer 32 on the back surface 2b side of the conductive substrate 2 was masked with tape to form the Cu-containing layer 41 on the front surface 2a side of the conductive substrate 2, and then the masking was removed, and the Cu-containing layers 41 and 42 were further formed on the front surface 2a side and the back surface 2b side of the conductive substrate 2, thereby forming the Cu-containing layers 41 and 42 of different thicknesses on the front surface 2a side and the back surface 2b side of the conductive substrate 2. In this manner, the composite materials 1 of the present invention examples and the comparative examples were obtained.

[0068] Here, when forming the Cu-containing layers 41 and 42 by electroplating, an aqueous solution containing copper sulfate with a copper (Cu) metal concentration of 200 g / L, 60 g / L of free sulfuric acid, and 50 g / L of free hydrochloric acid was prepared as the first-stage electroplating solution. Next, a plate-shaped conductive base of 20 cm long x 6 cm wide was placed in the plating electrolytic tank as a cathode electrode, and a plate-shaped phosphorus-deoxidized copper plate of 20 cm long x 6 cm wide was placed as an anode electrode facing both plate surfaces of the cathode electrode. 1 liter of electroplating solution was poured into the tank, and the plating solution was stirred at a temperature of 30°C with a stirrer rotation speed set to 100 rpm to 400 rpm at 1 A / dm 2 A Cu-containing layer (Cu-containing underlayer) having a thickness of 0.01 μm to 0.1 μm was formed by electroplating by passing a current at a current density of 1000 μm to 1000 μm. The formation of this Cu-containing underlayer was also performed immediately after removing the masking in Invention Examples 5, 6, 9, and 10 and Comparative Examples 2 and 5.

[0069] After forming the Cu-containing underlayer, an aqueous solution containing copper sulfate with a copper (Cu) metal concentration of 150 g / L, 100 g / L of free sulfuric acid, and 50 g / L of free hydrochloric acid was prepared as the second-stage electroplating solution. Next, 1 liter of the electroplating solution was placed in a plating electrolytic bath, and the solution was stirred at a temperature of 30°C with a stirrer speed set to 400 rpm at 5 A / dm 2 By passing a current at a current density of 1000 kPa (1000 MPa), Cu-containing layers 41 and 42 having the thicknesses shown in Table 1 were formed by electroplating.

[0070] On the other hand, in Comparative Example 6, a 100 μm thick stainless steel plate (SUS304) was sandwiched between 50 μm thick oxygen-free copper plates on both sides and cold-rolled to produce a clad material having a conductive substrate and a Cu-containing layer of the thicknesses shown in Table 1 as a composite material.

[0071] [Various measurement and evaluation methods] The conductive substrates used in the above-mentioned examples and comparative examples, and the composite materials obtained in the examples and comparative examples, were evaluated for the following characteristics. The evaluation conditions for each characteristic were as follows.

[0072] [1] Measurement of Vickers hardness (HV) of conductive substrate For the conductive substrates used in the present invention and comparative examples, the Vickers hardness test method described in JIS Z2244 (2009) was followed. A cross-sectional sample was prepared by embedding the conductive substrate as a test piece in resin and mechanically polishing a cross-section including the thickness direction. The Vickers hardness (HV) of the conductive substrate was measured when a diamond indenter was pressed into this cross-section with a load (test force) of 0.049 N and the pressing time of the indenter was 15 seconds.

[0073] [2] Measurement of the ratio of the cross-sectional area of ​​the Cu-containing layer to the total cross-sectional area of ​​the composite In the examples of the prepared composite materials in which the Cu-containing layers 41, 42 were formed on both sides of the conductive base 2, it was recognized that the front surface 41a and the back surface 41b of the Cu-containing layer 41 formed on one side of the conductive base 2 were both flat, the front surface 42a and the back surface 42b of the Cu-containing layer 42 formed on the other side of the conductive base 2 were both flat, and the front surface 1a and the back surface 1b of the composite material 1 were both flat. Therefore, in these examples, the ratio of the sum (t1+t2) of the thicknesses of the Cu-containing layers 41, 42 to the thickness t0 of the composite material 1 was defined as the ratio of the cross-sectional area of ​​the Cu-containing layers to the total cross-sectional area of ​​the composite material.

[0074] In addition, in the examples in which the Cu-containing layer 41 is formed on one side of the conductive base 2, it was recognized that the front surface 41a and the back surface 41b of the Cu-containing layer 41 formed on one side of the conductive base 2 were both flat, and the front surface 1a and the back surface 1b of the composite material 1 were both flat. Therefore, in these examples, the ratio of the thickness t1 of the Cu-containing layer 41 to the thickness t0 of the composite material 1 was defined as the ratio of the cross-sectional area of ​​the Cu-containing layer to the total cross-sectional area of ​​the composite material.

[0075] Here, the thickness t0 of the composite material 1 was measured with a micrometer, and the thickness t1 of the Cu-containing layer 41, the thickness t2 of the Cu-containing layer 42, and the thicknesses of the Ni-containing layers 31 and 32 were measured with an electrolytic film thickness meter (GCT-311 manufactured by Densoku Co., Ltd.). The results are shown in Table 2.

[0076] [3] Measurement of the average grain size in the Ni-containing layer of the composite The average grain size of the Ni-containing layers 31 and 32 was measured by forming a cross section including the thickness direction of the composite material 1 using a focused ion beam (FIB) device (FB2000A manufactured by Hitachi, Ltd.), and observing the cross section using a scanning ion microscope (SIM, manufactured by Seiko Instruments, model number: SMI3050TB). The number of points where lines parallel to the substrate intersect with the boundaries of the grains was counted from the channeling contrast (crystal orientation information) that appeared in the obtained SIM image, and the average grain size of the grains was obtained by a cutting method that obtains the average length of each section of the lines divided by the boundaries of the grains. Here, the observation of the cross section using the SIM was performed by randomly selecting three fields of view from the Ni-containing layers 31 and 32, with a horizontal range of 3 μm as one field of view, and the average grain size of the grains obtained for each of the three fields of view was taken as the average grain size [μm]. The results are shown in Table 2. In addition, when the Cu-containing layers 41, 42 were thick and it was difficult to form a cross section of the composite material 1, the Cu-containing layers 41, 42 were peeled off from the composite material 1 by electrolysis or electroless treatment, or the composite material 1 was thinned by etching, and then a cross section including the thickness direction having the Ni-containing layers 31, 32 was formed.

[0077] [4] The ratio of the total length of the laminate interface where the Ni crystal grains and Cu crystal grains facing each other across the laminate interface have the same crystal orientation to the total length of the laminate interface of the composite material. The ratio of the total length of the portion of the lamination interface 51, 52 where the Ni crystal grains 33, 34 and the Cu crystal grains 43, 44 facing each other across the lamination interface 51, 52 have the same crystal orientation to the total length of the lamination interface 51, 52 was calculated from the channeling contrast (crystal orientation information) of the three fields of view obtained in the measurement of the average crystal grain size contained in the Ni-containing layer [3] above, and the total length of the portion of the lamination interface 51, 52 where the Ni crystal grains 33, 34 and the Cu crystal grains 43, 44 facing each other across the lamination interface 51, 52 have the same crystal orientation was calculated, and these ratios were calculated. From the ratios calculated for each field of view, the average of the ratios for the three fields of view was taken as the measured ratio. The results are shown in Table 2.

[0078] Here, the length of the portion of the stacking interface 51, 52 where the Ni crystal grains 33, 34 and the Cu crystal grains 43, 44 facing each other across the stacking interface 51, 52 have the same crystal orientation is the sum of the length of the portion of the stacking interface 51, 52 where the dark-colored Ni crystal grains 33, 34 of the Ni-containing layers 31, 32 face the dark-colored Cu crystal grains 43, 44 of the Cu-containing layers 41, 42 in the channeling contrast described above, and the length of the portion of the stacking interface 51, 52 where the light-colored Ni crystal grains 33, 34 of the Ni-containing layers 31, 32 face the light-colored Cu crystal grains 43, 44 of the Cu-containing layers 41, 42 in the channeling contrast described above.

[0079] [5] Measurement and evaluation of tensile strength of composite materials The tensile strength was measured using three test pieces of No. 13B as specified in JIS Z2241, and the average value of the tensile strength obtained from the three test pieces was taken as the measured value. In this example, when the tensile strength was 800 MPa or more, the tensile strength was evaluated as being within the appropriate range and having excellent mechanical properties, and was given a rating of "◎". On the other hand, when the tensile strength was less than 800 MPa, the tensile strength was not within the appropriate range, and the mechanical properties were unsatisfactory, and was given a rating of "×". The results are shown in Table 2.

[0080] [6] Measurement and evaluation of electrical conductivity of composite materials The conductivity was measured three times using the four-terminal method, and the average of the three measurements was used as the measured conductivity. In this example, when the conductivity was 20% IACS or more, the conductivity was within the appropriate range and the conductivity was excellent, and the result was evaluated as "◎". On the other hand, when the conductivity was less than 20% IACS, the conductivity was not within the appropriate range and the result was unsatisfactory in terms of conductivity, and the result was evaluated as "×". The results are shown in Table 2.

[0081] [7] Measurement and evaluation of adhesion of Cu-containing layers in composite materials The composite materials 1 obtained in the present invention and comparative examples were evaluated for the presence or absence of peeling of the Cu-containing layers 41 and 42 from the composite materials by a tape peeling test specified in JIS H 8504. Here, in the tape peeling test, before attaching the tape, a sharp blade was used to form a streak that reached the conductive substrate 2 on the surfaces of the Cu-containing layers 41 and 42 so as to form a square with a side of 2 mm. The tape peeling test was performed on both of the Cu-containing layers 41 and 42 formed on both sides of the conductive substrate 2 (in an example in which the Cu-containing layer was formed on only one side of the conductive substrate 2, the tape peeling test was performed on the Cu-containing layer formed on one side). When no peeling occurred in the Cu-containing layer in any sample, the Cu-containing layer was evaluated as having excellent adhesion to the substrate and was marked with "◎". In addition, in cases where at least one sample showed minute peeling near the scratches, but the peeling did not spread to the Cu-containing layer inside and outside the scratches, the Cu-containing layer was deemed to have high adhesion to the substrate and was evaluated as "Good." On the other hand, in cases where at least one sample showed peeling spreading to the Cu-containing layer inside and outside the scratches, the Cu-containing layer was deemed to have failed in terms of adhesion to the substrate and was evaluated as "Poor." The results are shown in Table 2.

[0082] [8] Overall rating Among these evaluation results, the three evaluation results related to the tensile strength, the electrical conductivity, and the adhesion of the Cu-containing layer were all rated as "◎", which means that the mechanical properties and electrical conductivity are all high, and that the adhesion to the substrate is particularly high. In addition, among these three evaluation results, the tensile strength and the electrical conductivity were rated as "◎" and the adhesion of the Cu-containing layer was rated as "〇", which means that the mechanical properties and electrical conductivity are all high, and that the adhesion to the substrate is good. On the other hand, if at least one of these three evaluation results was rated as "×", it was rated as "×" because at least one of the mechanical properties and the electrical conductivity was unsatisfactory, or the adhesion to the substrate was unsatisfactory. The results are shown in Table 2.

[0083] [Table 1]

[0084] [Table 2]

[0085] From the results of Tables 1 and 2, the composite materials 1 of Examples 1 to 13 of the present invention have Ni-containing layers 31, 32 and Cu-containing layers 41, 42 laminated in this order on one or both sides of the conductive base 2 made of an Fe-based alloy, and the total thickness of the Cu-containing layers 41, 42 and the ratio of the cross-sectional area of ​​the Cu-containing layers 41, 42 to the total cross-sectional area of ​​the composite material 1 were within the appropriate ranges of the present invention. In this case, the composite materials 1 of Examples 1 to 13 of the present invention were evaluated as "◎" or "◯" in the three evaluation results regarding the tensile strength, electrical conductivity, and adhesion of the Cu-containing layer, and were also evaluated as "◎" or "◯" in the overall evaluation.

[0086] Fig. 2 shows a scanning ion microscope (SIM) image of a cross section including the thickness direction of the composite material of Example 9. From the channeling contrast (crystal orientation information) shown in the scanning ion microscope (SIM) image of Fig. 2, it is understood that the composite material of Example 9 of the present invention has Ni-containing layers 31, 32 and Cu-containing layers 41, 42 laminated in this order on one or both sides of the conductive substrate, and that the Ni-containing layers 31, 32 and the Cu-containing layers 41, 42 each contain crystal grains.

[0087] Therefore, all of the composite materials 1 of Inventive Examples 1 to 13 met the acceptable standards for the three performances of tensile strength, electrical conductivity, and adhesion of the Cu-containing layer, and were overall evaluated as "Excellent" or "Good."

[0088] On the other hand, the composite material of Comparative Example 1 did not have any of the Ni-containing layers 31 and 32. In Comparative Examples 2 and 5, the total thickness of the Cu-containing layers 41 and 42 was smaller than the appropriate range of the present invention. In Comparative Examples 3 and 4, the ratio of the cross-sectional area of ​​the Cu-containing layers 41 and 42 to the total cross-sectional area of ​​the composite material 1 was larger than the appropriate range of the present invention. Therefore, at least one of the three performance evaluations regarding the tensile strength, electrical conductivity, and adhesion of the Cu-containing layer was poor, and the overall evaluation was "x". [Explanation of symbols]

[0089] 1 Composite material 1a Composite surface 1b Back side of composite material 10 Measurement area for composite materials 2. Conductive substrate 2a Surface of conductive substrate 2b Back side of conductive substrate 31, 32 Ni-containing layer 33, 34 Ni grains 41, 42 Cu-containing layer 41a, 42a Surface of Cu-containing layer 41b, 42b Back side of Cu-containing layer 43, 44 Cu grain 51, 52 Laminated interface t0 composite thickness t1, t2 Thickness of Cu-containing layer t3, t4Thickness of Ni-containing layer t5 Conductive substrate thickness L1~L 10 The length of the portion of the laminate interface where Ni crystal grains and Cu crystal grains on either side of the laminate interface have the same crystal orientation

Claims

1. A composite material comprising a conductive substrate made of an Fe-based alloy, a Ni-containing layer and a Cu-containing layer laminated in this order on one or both sides of the conductive substrate, When viewed in a cross section including a thickness direction of the composite material, The Cu-containing layer has a total thickness of 10 μm or more, and A composite material, wherein a ratio of a cross-sectional area of ​​the Cu-containing layer to a total cross-sectional area of ​​the composite material is 0.20 or more and 0.60 or less.

2. The composite material according to claim 1 , wherein the Fe-based alloy is an Fe—Ni—Cr-based or Fe—Ni-based alloy.

3. 10. The composite of claim 1, wherein the Ni-containing layer has grains with an average grain size of 1.00 μm or less.

4. 2. The composite material according to claim 1, wherein, when the lamination interface between the Ni-containing layer and the Cu-containing layer is viewed in the cross section, a ratio of a total length of a portion of the lamination interface in which Ni crystal grains constituting the Ni-containing layer and Cu crystal grains constituting the Cu-containing layer facing the Ni crystal grains across the lamination interface have the same crystal orientation to a total length of the lamination interface in a measurement region is 0.2 or more.

5. 2. The composite material according to claim 1, wherein the conductive substrate has a Vickers hardness (HV) of 300 or more.

6. An electric / electronic component comprising the composite material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-strength clad material having excellent tensile strength

    JP1999104856A

  • Heat diffusion composite metal sheet and heat diffusion part

    JP2020025097A